Analytical and Clinical Evaluation of “AccuPower SARS-CoV-2 Multiplex RT-PCR kit (Bioneer, South Korea)” and “Allplex 2019-nCoV Assay (Seegene, South Korea)” for SARS-CoV-2 RT-PCR Diagnosis: Korean CDC EUA as a Quality Control Proxy for Developing Countries - Freire-Paspuel, Byron; Garcia-Bereguiain, Miguel Angel (Frontiers in Cellular and Infection Microbiology, 2021)
Background Multiple RT-qPCR kits are available in the market for SARS-CoV-2 diagnosis, some of them with Emergency Use Authorization (EUA) by FDA or their country of origin agency, but many of them lack of proper clinical evaluation. Objective We evaluated the clinical performance of two Korean SARS-CoV-2 RT-PCR kits available in South America, AccuPower SARS-CoV-2 Multiplex RT-PCR kit (Bioneer, South Korea) and Allplex 2019-nCoV Assay (Seegene, South Korea), for RT-qPCR SARS-CoV-2 diagnosis using the CDC protocol as a gold standard. Results We found strong differences among both kits clinical performance and analytical sensitivity; while the Allplex 2019-nCoV Assay has sensitivity of 96.5% and an estimated limit of detection of 4,000 copies/ml, the AccuPower SARS-CoV-2 Multiplex RT-PCR kit has a sensitivity of 75.5% and limit of detection estimated to be bigger than 20,000 copies/ml. Conclusions AccuPower SARS-CoV-2 Multiplex RT-PCR kit and Allplex 2019-nCoV Assay are both made in South Korea but EUA by Korean CDC was only granted to the later. Our results support that Korean CDC EUA should be considered as a quality control proxy for Korean SARS-CoV-2 RT-PCR kits prior to importation by developing countries to guarantee high sensitivity diagnosis.